Evaluation of Problem-Based Learning Experiences Addressing Health Promotion in the Fourth Grade of Primary School - Beatriz Mederer-Hengstl; Pilar Núñez-Delgado; Aurora Bueno-Cavanillas (MDPI AG, 2024)
Background: The global issues of overweight and sedentary lifestyles require comprehensive responses from health systems. Despite this, health education remains fragmented and sporadic. This study aims to target primary school children to instil healthy habits using active learning strategies, with a specific focus on promoting a healthy diet and physical activity. Methods: This study employed problem-based learning (PBL) projects with fourth-grade primary students to encourage the acquisition of healthy habits. Conducted over four consecutive years at a two-line school, the study utilised an opportunity sample, evaluating intervention and control groups by comparing their corresponding scores. The control groups consisted of 54 students, while the intervention group included 159 students. Data collection involved pre-test and post-test questionnaires to measure outcomes. Results: Differential evaluation scores revealed significantly higher results in the intervention groups compared to the control groups, with an average score increase of 3.62 points in control groups and 6.94 points in intervention groups, particularly in attitudinal competencies. The strategies employed facilitated the development of crucial skills such as information search, synthesis, representation, analysis, decision making, teamwork, and intrapersonal awareness. Additionally, they significantly broadened the knowledge acquired regarding healthy habits. Conclusions: The problem-based learning approach proved effective in helping children understand the importance of making healthy choices and encouraged the integration of such habits into their daily lives. These findings suggest that active learning strategies can significantly enhance health education and promote long-term healthy behaviours among primary school children.